Determinantes para o internamento na Unidade de Terapia Intensiva de crianças e adolescentes com COVID-19 no estado da Paraíba: da regressão logística à análise multinível - Damascena, Lecidamia Cristina Leite (2022)
In developing countries, the incidence of COVID-19 in children and adolescents may be affected by the social vulnerability of some underprivileged classes. Therefore, the need to investigate the determinants associated with social inequalities and individual factors that can lead to hospitalization of children and adolescents with COVID-19 in the ICU of the state of Paraíba becomes relevant in the current context of a pandemic and makes it possible to the development of tools that assist in the decision-making processes of managers, health professionals and patients. Thus, the objective of this work was to identify the individual and contextual determinants of social vulnerability associated with hospitalization in the Intensive Care Unit of children and adolescents diagnosed with COVID-19 in Paraíba. It is a retrospective, exploratory, analytical study, with a quantitative approach, with the aim of identifying how social inequalities influence the morbidity and mortality rates of COVID-19 in children and adolescents. The population included children and adolescents from the state of Paraíba who presented symptoms suggestive of COVID-19 and who were notified through the Severe Acute Respiratory Syndrome (SRAG) form. The sample consisted of all confirmed COVID-19 cases involving individuals under the age of 19. The data provided by the State Health Department of the State of Paraíba were worked on, from April 2020 to June 2021. Initially, a descriptive analysis of the data was performed, using means, median, standard deviation, percentage and absolute frequencies to outline the profile of children and adolescents witch COVID-19. Then, logistic regression and models multilevel analysis were applied, using the R software, version 4.1.1. The descriptive analysis revealed that the predominance of COVID-19 records occurred in females (57.0%; n=277), the median age was 6 years (±7.14) and most of them self-reported as brown (75 .8%; n=326). The condition of being pregnant did not apply to most patients (74.1%; n=354). The median number of days from symptom onset to notification was 6.16 days (±12.3). Among the signs, the most frequent was fever (65.9%; n=298) and the most reported comorbidities were neurological problems (19.1%; n=26). At admission, 55.4% (n=246) did not need ventilatory support, 58.4% (n=171) did not undergo X-ray and 73.0% (n=355) did not need intensive care. Regarding social context, notifications are concentrated in individuals living in urban areas (85.5%; n=384), residents of João Pessoa (28.5%; n=139), large cities (55.1 %; n=268), population density above 165.52 inhabitants/km² (49.8%; n=242), high IDHM (44.7%; n=217); with low IVS (47.5%; n=231). Logistic regression shows that the variables that influence the ICU admission are age (OR=0.94, 95%CI=0.90-0.97), male sex (OR=1.98; 95%CI=1.18- 3.32), cough (OR=0.32, 95%CI=0.18-0.59), fever (OR=0.42, 95%CI=0.23-0.74), respiratory distress (OR= 2.43, 95%CI=1.29-4.56), dyspnea (OR=3.56, 95%CI=1.77-7.17), large population (OR=2.70, 95%CI=1 .07-6.76). The multilevel analysis revealed that age (OR=0.80, 95%CI=0.78-0.81), population size (OR=0.93, 95%CI=0.92-0.93) and dyspnea (OR=0.99, 95%CI=0.99-0.99) associated with the occurrence of the outcome. The patient's conditions and the social and economic context in which children and adolescents belong appear to have repercussions in different proportions on the worsening of SARS-CoV-2 infection, requiring intensive care.